2014
DOI: 10.3390/ijms150813833
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin-Induced Apoptosis in HGF-Stimulated Lens Epithelial Cells by AKT/mTOR, ERK and JAK2/STAT3 Pathways

Abstract: Hepatocyte growth factor (HGF) induced the proliferation of lens epithelial cells (LECs) and may be a major cause of posterior capsule opacification (PCO), which is the most frequent postoperative complication of cataract surgery. To date, several agents that can block LECs proliferation have been studied, but none have been used in clinic. Recently, accumulating evidence has suggested rapamycin, the inhibitor of mTOR (mammalian target of Rapamycin), was associated with the induction of apoptosis in LECs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…RAPA has been demonstrated to activate autophagy in epithelial cells. 34 In previous study, 32 we discovered that RAPA treatment promoted the expression of ATG7, and Atg7-mediated autophagy did appear in the gastrulation stage of early embryonic development. We incubated chick embryos (HH0) in the presence of 40nM of RAPA until they reached stage HH11, when the heart tube has formed.…”
Section: Rapamycin-induced Autophagy Increases Risk Of Cardia Bifidamentioning
confidence: 91%
“…RAPA has been demonstrated to activate autophagy in epithelial cells. 34 In previous study, 32 we discovered that RAPA treatment promoted the expression of ATG7, and Atg7-mediated autophagy did appear in the gastrulation stage of early embryonic development. We incubated chick embryos (HH0) in the presence of 40nM of RAPA until they reached stage HH11, when the heart tube has formed.…”
Section: Rapamycin-induced Autophagy Increases Risk Of Cardia Bifidamentioning
confidence: 91%
“…UV radiation, aging, hypoxia, and other stimuli could cause excess apoptosis of lens epithelial cells, thus causing cytoskeletal degradation, accumulation of crystal protein, and ultimately cataract. 37 It has been approved that the apoptosis of lens epithelial cells is much more different in high myopia cataract and ordinary age-related cataract patients. We analyzed lens capsule gene microarray data in high myopia patients and identified two differentially expressed genes: Krüppellike factor 6 (KLF6) and ATF4.…”
Section: Discussionmentioning
confidence: 99%
“…This experiment was repeated 3 times. 37,38,39 Statistics All data were expressed as mean±SD. All experiments were performed at least three times.…”
Section: Rna Extraction Reverse Transcription and Quantitative Revementioning
confidence: 99%
“…Many prior studies have provided evidence indicating that the ERK1/2 pathway is regulated mostly by mitogenic stimuli, and leads to the production of proteins required for cell growth and differentiation ( Craig et al ., 2008 ; Kim and Choi, 2010 ; Munshi and Ramesh, 2013 ). However, more recently, several studies have demonstrated that inhibition of ERK signaling leads to increased sensitivity of anticancer drug ( Ohmichi et al ., 2005 ; Tian et al ., 2014a ; Tian et al ., 2014b ). ERK activation induces the deveploment of B cell ( Gold, 2008 ) and activation of ERK is also involved in the inducation of apoptosis in neuronal and various cancer cells ( Agrawal et al ., 2014 ; Deschenes-Simard et al ., 2014 ; Esmaeili et al ., 2014 ).…”
Section: Discussionmentioning
confidence: 99%